PENGEMBANGAN E-LKPD BERBASIS MODEL PEMBELAJARAN PROBLEM SOLVING LEARNING PADA PEMBELAJARAN TEMATIK DI SEKOLAH DASAR - Selli Putri Auliawati Alfaro; Ana Nurhasanah; Ratna Sari Dewi (STKIP Subang, 2023)
This study aims to develop E-LKPD learning media based on problem solving learning models in thematic learning in class V SD and to produce E-LKPD learning media based on problem solving learning models that meet the criteria of being feasible to implement in thematic learning in class V. Methods the research used is the research and development method modified by Trianto, namely define, design, develop, and disseminate. This learning media is subjected to expert validation tests conducted by media experts, material experts and language experts. After a validation test was carried out by a team of experts, a product trial was then carried out with the research subject, namely fifth grade elementary school students. The results of the media expert test showed that this learning media obtained an average score of 88% in the